COUNTRY, VILLAGE, STEPPE: THE PROBLEM OF PROVINCE IN A.P CHEKHOV’S WORKS (Proceedings of Southern Federal University. Philology, 2013)
Kondratyeva V.V.Keywords: Anton Chekhov’s works, images of village, steppe, mythopoetic category, short stories and novels.In the article the image of province in Anton Chekhov’s works is analyzed as a historical and cultural phenomenon. In the structure of the central spatial images of village, steppe, steppe-house the details, associated with the motives of boredom, melancholy and anxiety, are aggravating. The signs of chaos are the essential characteristics of existence in the province. The space of the province is endowed with the features of an alien world. Mythopoetic category of a ‘stranger’ gets a philosophical tone in the stories, the events of which take place in the steppe. In the area of the vast, colorful world of the steppe take place and develop life stories, full of drama and ordinary everyday life.